State transfers, taxes and income inequality in Brazil - Medeiros, Marcelo (2015)
Using a factor decomposition of the Gini coefficient, we measure the contribution to inequality of direct monetary income flows to and from the Brazilian State. The income flows from the State include public sector workers' earnings, Social Security pensions, unemployment benefits, and Social Assistance transfers. The income flows to the State comprise direct taxes and employees' social security contributions. Data come from the Brazilian POF 2008–09. We do not measure indirect contributions to inequality of subsidies granted to and taxation of companies, nor the in-kind provision of goods and services. The results indicate that the State contributes to a large share of family per capita income inequality. Incomes associated with work in the public sector—wages and pensions—are concentrated and regressive. Components related to the private sector are also concentrated, but progressive. Contrary to what has been found in European countries, public spending associated with work and social policies is concentrated in an elite group of workers and, taken as a whole, tends to increase income inequality. Redistributive mechanisms that could reverse this inequality, such as taxes and social assistance, are very progressive but proportionally small. Consequently, their effect is completely offset by the regressive income flows from the State.